CPR related injuries of the chest wall: direct and indirect fractures - Schenderlein, Anne; Groh, Johannes; Kern, Florian; Perl, Mario; Schulz-Drost, Stefan (European Journal of Trauma and Emergency Surgery, 2025)
BACKGROUND: Rib and sternum fractures are common injuries associated with cardiopulmonary resuscitation (CPR). The fracture mechanism is either direct by application of force on sternum and anterior ribs or indirect by bending through compression of the thorax. The aim of this study was to determine morphologies of rib fractures after CPR and to reevaluate prior findings on fracture localisation, type and degree of dislocation. METHODS: The present study was based on all inpatients treated for chest wall fractures after non traumatic cardiac arrest at a Level 1 Trauma Centre from 2010 to 2016 who had received CT scans. Each fracture was analyzed for location, degree of dislocation and fracture type classified according to AO/OTA and CWIS. We also analysed Fracture Line orientation. RESULTS: We enrolled 40 patients with a total of 423 rib fractures. We found most fractures anterolaterally between the 3rd to 6th rib symmetrically on both sides of the thorax. We found sternum fractures in 30% of the patients, 50% being located at the at the corpus sterni between rib 3 and 4. All patients with sternum fractures suffered from rib fractures and most had fractures of the cartilage or osteochondral junction. All cartilage fractures were straight, undisplaced type A fractures. Most indirect fractures occurred anterolaterally between 50 and 60° in the axial plane. More than 90% of those fractures were classified as type A, 70% showed a straight fracture line and 60% were undisplaced. There was no difference in degree of dislocation between straight and oblique fracture lines. We found 143 incomplete fractures. CONCLUSION: We confirmed prior findings regarding fracture patterns in CPR related injuries. We observed approximately 2-3 times as many straight-lined fractures as oblique ones following indirect trauma. One third of all fractures are incomplete, these highlights the special characteristics like high elasticity of ribs.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Chest wall injury; CPR; Flail chest; Fracture morphology; Indirect fractures; Rib fractures